(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of gastro-esophageal reflux disease and associated factors in medical college students Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Nishtar Medical and Dental College, Multan in Medicine Department, for 06 months from February 2024 to July 2024. Methods: Total 301 medical students were enrolled. Consent and demographic detail was taken. The students after meeting selection criteria were enrolled by using non-probability convenient sampling method. A validated FSSG assessment tool was used to diagnose the presence of GERD in students. Life style factors, medical factors and eating habits of students were taken of predesigned questionnaire. All the data was entered and analyzed on SPSS version 26. Results: The mean age of the students was 20.15±1.95 years, and the average FSSG score was 8.10±5.37. Based on the FSSG score, GERD was present in 84 students (27.91%). Among students with inadequate sleep, 44% had GERD, while 31.8% did not (p-value = 0.046). Regarding eating habits, frequent consumption of soft drinks, fried foods, and spicy meals significantly affected the presence of GERD (p-value < 0.05). Among students with associated dyspepsia, 17.9% had GERD, while 9.6% did not (p-value = 0.003). Similarly, among students using over-the-counter analgesics, 36.9% had GERD compared to 24.9% without it (p-value = 0.038). Conclusion: This study concluded that one-fourth of medical students experience gastroesophageal reflux disease. Factors such as inadequate sleep, certain eating habits, family history of peptic or duodenal ulcers, associated dyspepsia, and the use of over-the-counter drugs are significantly associated with the presence of GERD in medical students